Pengaruh Bauran Promosi Terhadap Minat Beli Iphone Mahasiswa Universitas MDP Palembang - Anggellin - -; Megawati Megawati (Universitas Multi Data Palembang, 2026)
The rapid development of technology has made smartphones, especially iPhone, a primary need and lifestyle for students. This study aims to determine the effect of the promotion mix on the buying interest of iPhone among students at MDP University Palembang. Using a quantitative associative method, data were collected from 328 respondents through purposive sampling. The results of the simple linear regression analysis show a constant value of 1.679 and a regression coefficient of 0.312. Hypothesis testing (t-test) resulted in a t-count of 6.124 > t-table 1.968 with a significance of 0.000, meaning the promotion mix significantly affects buying interest. The coefficient of determination (Adjusted R Square) is 0.699, indicating that the promotion mix contributes 69.9% to buying interest, while the remaining 30.1% is influenced by other variables. In conclusion, an effective promotion strategy is a key factor in increasing student interest in iPhone products.